Two-dimensional computational modeling of high-speed transient flow in gun tunnel - Mohsen A.M.; Yusoff M.Z.; Hasini H.; Al-Falahi A. (Springer New York LLC, 2023)
In this work, an axisymmetric numerical model was developed to investigate the transient flow inside a 7-meter-long free piston gun tunnel. The numerical solution of the gun tunnel was carried out using the commercial solver Fluent. The governing equations of mass, momentum, and energy were discretized using the finite volume method. The dynamic zone of the piston was modeled as a rigid body, and its motion was coupled with the hydrodynamic forces from the flow solution based on the six-degree-of-freedom solver. A comparison of the numerical data with the theoretical calculations and experimental measurements of a ground-based gun tunnel facility showed good agreement. The effects of parameters such as working gases and initial pressure ratio on the test conditions in the facility were examined. The pressure ratio ranged from 10 to 50, and gas combinations of airair, heliumair, airnitrogen, and airCO2 were used. The results showed that steady nozzle reservoir conditions can be maintained for a longer duration when the initial conditions across the diaphragm are adjusted. It was also found that the gas combination of heliumair yielded the highest shock wave strength and speed, but a longer test time was achieved in the test section when using the CO2 test gas. Springer-Verlag GmbH Germany 2017.